Effects of a SWELE program for improving mental wellbeing in children and adolescents with special educational needs: protocol of a quasi-experimental study - Regina Lai Tong Lee; Sally Wai Chi Chan; Yuen Yu Chong; Steven Wai Ho Chau; Kai Chow Choi; Wai Tong Chien (BMC Pediatrics)
Abstract Background Unstructured play has also been found effective on promoting positive emotions and emotional competence among children and adolescents with special educational needs (SEN). Unstructured Outdoor Play coupled with Mindfulness-based Interventions via ‘Supporting Wellness in E-Child Learning Environments’ (SWELE) program can foster the mental health and wellbeing of children and adolescents with SEN. Currently there is a lack of the unstructured play with mindfulness-based interventions in the special schools in Hong Kong. Thus, aim of the SWELE program is to examine the effects of unstructured play with mindfulness-based interventions—(SWELE) program combining unstructured outdoor play activities with mindfulness-based interventions to promote mental wellbeing among SEN children and adolescents. Methods This 16-week SWELE program focuses on combining unstructured outdoor play activities with mindfulness-based interventions to promote mental wellbeing among children and adolescents with SEN. Training workshops for schoolteachers, school principals, parents and student mental health ambassadors in each special school together with a 16-week SWELE program and each last 45–60 min. Unstructured play allows students the freedom to explore, create and discover without predetermined rules or guidelines. Outdoor unstructured play activities include naturally run, jump and move on a playground, riding a bike, climbing trees, playing tag, playing with blocks, colour, water play, and boxes. A convergent parallel mixed-methods design both with a quantitative measure using a single group pre- and post-tests quasi-experiment behavioural observational method to preliminarily evaluate the impact of SWELE Program on SEN children’s and adolescents’ mental wellbeing; and with a qualitative design to conduct eight focus group discussions including schoolteachers, school principals, parents, SEN students, school nurses from six selected special groups and to explore their perceptions and experiences after participated the SWELE program. Discussion The purpose of this protocol is to examine the effects of a 16-week SWELE program on the mood, anxiety level, social skills and playfulness behaviours among children and adolescents with SEN in the special schools in Hong Kong. From the evaluation and observation, the pre-set aim and objectives on the improvement of mental wellbeing in children and adolescents with SEN can be confirmed. Trial registration ClinicalTrial.gov, NCT06112483. Registered on 31 October 2023.